A case of persistent hiccups successfully managed with pregabalin. (August 2015) - Groninger, Hunter; Cheng, M. Jennifer
<x content-type="archive" xml:space="preserve">Abstract</x> A patient with end-stage Ewing's sarcoma presented with persistent, disabling hiccups in a clinical setting in which common pharmacotherapies were either contraindicated or refused. Initiation of pregabalin, with titration to effective dose, significantly diminished hiccups within 72 hours, with no adverse effects, suggesting a potential niche for this drug.